VD_FINDINFO HC / 2011 / 574 vom 30. August 2011 - VD Tribunal cantonal (2011)
ASSISTANCE JUDICIAIRE, AVOCAT D'OFFICE | 117 CPC (CH), 119 CPC (CH), 121 CPC (CH), 319 let. b ch. 1 CPC (CH), 320 CPC (CH), 321 CPC (CH)